Studi Analisis Perdarahan di Luar Siklus Menstruasi pada Wanita Usia Subur - sholihah, andri nur; Mahmudah, Nurul (STIKES Ngesti Waluyo, 2023)
Bleeding outside the menstrual cycle often raises many questions for women in childbearing age. The bleeding is an unusual thing to happen, therefore it causes worries for women who experience it. Women with this condition often seek health care to find a solution. The causes of this bleeding are varying, mostly depending on the age and stage of the woman's life. The purpose of this study is to identify the characteristics of women of childbearing age who experience bleeding outside the cycle, which include the characteristics of age, education, occupation, marital status and duration of bleeding. The research method used was descriptive quantitative. The population of the study was women of childbearing age who experience bleeding outside the menstrual cycle in Sleman Hospital, Yogyakarta Special Region. The sampling techniques used was purposive sampling technique. The results of this study showed that most respondents are in the age group of 36-49 years (96 respondents; 93.2%), have a high school education level (75 respondents; 72.8%), and mostly housewives (56 respondents; 54.4%). Furthermore, from the marital status characteristics, most subjects are married (99 respondents; 96.1%), and from the bleeding characteristics, the bleeding mostly lasts for 2 days (59 respondents; 57.3%). Suggestions for further research is research that can develop a wider variable.